Needs of early-career professionals in STM: Findings from two surveys - Erin Foley; Rachel Moriarty; Kerys Martin (European Science Editing)
Background: The Early Career Publishers Committee (ECPC) of the STM Association (the International Association of Scientific, Technical, and Medical Publishers)’s Early Career Publishers Committee (ECPC) aims to engage, and provide tools and resources for, early-career publishers (ECPs) and professionals. The committee believes it is important to survey the community regularly to understand the background, needs, and concerns of its members to better achieve the committee’s goals.Objectives: Early-career professionals were surveyed in 2014 and 2020: the first survey was undertaken to get a baseline understanding of the community and to guide the newly formed ECPC whereas the second not only sought to review some aspects of the first survey but also to identify and explore ways to improve engagement and support through new or revised survey questions.Methods: The two surveys were conducted online through the ECPC mailing list and social networks. The surveys were voluntary, with the option to skip some questions, and responses – some in the form of a rating scale – were collected anonymously. Each survey remained open for over a month to maximize responses, but neither was pretested. Some questions in the first survey were revised in the second in the light of learnings from the first survey.Results: Most of respondents were women, 25–54 years old, from the UK or the US, with higher degrees, and working in editorial roles. In the second survey, many respondents were interested in developing their career either in their current role or in a different one, and nearly half were actively seeking a new role. Over half said that finding the right role was a challenge. Many had never participated in a publishing-related mentoring scheme, and most had not heard of the STM mentoring scheme before.Conclusions: More tools, resources, and outreach for entry-level and younger industry members, for those from countries outside the UK and US, and for those seeking to develop their careers may be useful in the future. The mentoring scheme could be publicized more prominently to drive engagement. A new survey will be needed in the next 2–3 years, given the potential impact of the COVID-19 global pandemic on the number of respondents in the second (2020) survey and their motivation.